Lubricant Spin-off and Oxidation Phenomenon on Hard Disk Media - Akinobu Wakabayashi (Japanese Society of Tribologists, 2009)
High temperature (hot) and high humidity (wet) effects on perfluoropolyether lubricants, Z-dol and Z-tetraol, were investigated using the high speed spin-tester. The study has shown that: (1) higher humidity accelerates the lubricant spin-off on the disk surface, (2) in the case of Z-tetraol, oxidative reaction occurs under the hot-dry condition, but not under the hot-wet condition, (3) aforementioned phenomenon occurs only when the mobile fraction is present, and (4) the oxidation occurs the more strongly, the closer the location is to the spindle shaft. An NMR analysis of bulk materials heated in 150 oC revealed that the oxidative chemical changes are confined within the end-groups of Z-tetraol. No change was observed from bulk Z-dol heated similarly.